Detection of antifungal activity of plant extracts on Alternaria citrus - Triaca,Tatiane (2018)
ABSTRACT For approximately 15 years, Brazilian citriculture has suffered considerable losses in productivity and fruit quality as a result of the attack by the phytopathogen Alternaria alternata f.sp. citri, which causes Alternaria brown spot (ABS). The disease control is still performed with the massive use of agrochemicals, reaching up to twenty applications per reproductive period. The present study evaluated the efficiency of in vitro and in vivo ABS control by using fermented extracts of Trifolium pratense and Daucus pusillus as a means to control the disease. Fermented extracts autoclaved at 40% showed 100% inhibition, while the crude extract of both plants had no inhibitory effect. In vivo, the best results were found with the preventive test of non-autoclaved Trifolium pratense, which inhibited the onset of the disease by 93%.